Educators' Perceptions on the Teaching of Philosophy in Schools in Barranquilla, Colombia - Nieto Mendoza, Isaac (2025)
This study explored the perceptions of 101 educators from public institutions in Barranquilla, Colombia, regarding the teaching of philosophy in secondary education in 2023. A quantitative, cross-sectional descriptive methodology was applied, utilizing a validated Likert scale with high reliability (α = 0.992). Results indicated that in terms of teaching methods, 61.4% and 22.8% of professors reported low and very low effective implementation, respectively (mean = 2.03). Teaching outcomes showed that 61.4% perceived overall results as low, with 22.8% reporting very low outcomes (mean = 2.03). Regarding challenges and barriers to teaching philosophy, the majority of teachers (59.4%) indicated a very low perception of significant obstacles, with 31.7% reporting a low perception (mean = 1.51). Overall, 22.8% of educators held a very low perception of philosophy teaching, while 61.4% expressed a low perception, suggesting a predominantly negative assessment (mean = 2.03). Despite low teaching outcomes, teachers’ perceptions suggest that challenges and barriers are not widely recognized as critical factors, indicating a possible lack of awareness regarding obstacles to educational quality. It is therefore recommended to enhance teacher training to improve the effectiveness of teaching methods and better align them with the current needs of the educational context.